Community-Based Social Marketing in Theory and Practice: Five Case Studies of Water Efficiency Programs in Canada. (December 2020) - Fries, Sarah; Cook, Julie; Lynes, Jennifer Kristin
Background: Community-based social marketing (CBSM) offers a pragmatic five-step approach to developing a program that fosters sustainable behaviour. However, how the CBSM theoretical framework has been implemented into practice remains largely under-evaluated. To help address this gap, Lynes et al. developed 21 benchmarks to assess CBSM programs. This research builds upon these benchmarks by using both the benchmarks and additional assessment criteria to assess five Canadian programs that have used CBSM principles. Focus: This paper is related to research and evaluation of community-based social marketing. Research Question: How has the CBSM theoretical framework been implemented in practice at the community level? Importance to the Social Marketing Field: By exploring how five Canadian programs have implemented CBSM, this paper enables practitioners to align their programs with CBSM principles more closely. It also contributes to the literature on CBSM effectiveness. Methods: Five qualitative case studies were assessed, each featuring a Canadian community program seeking to influence residential water efficiency behaviour. In order to systematically assess each program's adherence to the CBSM theoretical framework, a CBSM benchmark assessment tool that proposes additional assessment criteria to Lynes et al.'s 21 benchmarks was developed. The assessment tool allowed for replicable benchmark assessments across multiple programs. Triangulation of data from both primary (survey and interview) and secondary (peer-reviewed literature, gray literature, and online reporting) data sources informed the assessment of each case study. Results: On average, over the five case studies, just over half of the 21 benchmark criteria were fully integrated into the programs, whereas just under a third were partially integrated, and approximately one fifth were not integrated at all. Recommendations for Research or Practice: While the benchmarks were fairly well integrated overall, this paper outlines several recommendations that programs may consider to improve alignment with the CBSM theoretical framework and benchmarks. Recommendations for future research to explore CBSM effectiveness are also made. Limitations: Lack of generalizability due to small sample size, unable to make assessments of programmatic success, and inherent limitations of the benchmark assessment tool.